2014
DOI: 10.1038/cdd.2014.191
|View full text |Cite
|
Sign up to set email alerts
|

A novel RIPK4–IRF6 connection is required to prevent epithelial fusions characteristic for popliteal pterygium syndromes

Abstract: Receptor-interacting protein kinase 4 (RIPK4)-deficient mice have epidermal defects and fusion of all external orifices. These are similar to Bartsocas-Papas syndrome and popliteal pterygium syndrome (PPS) in humans, for which causative mutations have been documented in the RIPK4 and IRF6 (interferon regulatory factor 6) gene, respectively. Although genetically distinct, these syndromes share the anomalies of marked pterygia, syndactyly, clefting and hypoplastic genitalia. Despite the strong resemblance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 46 publications
4
41
0
4
Order By: Relevance
“…In addition to IRF6, RIPK4 can also activate NF-κB and JNK [12,13], and in vivo studies have revealed that appropriately balanced NF-κB and JNK activation is important for normal keratinocyte differentiation [36,37]. However, we found that Ripk4 S378X can activate NF-κB, which is consistent with a recent report that similarly demonstrated normal NF-κB activation by a human RIPK4 S376X mutant [38]. The p.Ser378X mutation also did not appear to affect the ability of Ripk4 to activate JNK.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to IRF6, RIPK4 can also activate NF-κB and JNK [12,13], and in vivo studies have revealed that appropriately balanced NF-κB and JNK activation is important for normal keratinocyte differentiation [36,37]. However, we found that Ripk4 S378X can activate NF-κB, which is consistent with a recent report that similarly demonstrated normal NF-κB activation by a human RIPK4 S376X mutant [38]. The p.Ser378X mutation also did not appear to affect the ability of Ripk4 to activate JNK.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were not particularly surprising given that the kinase domain of RIPK4 had previously been shown to be sufficient for NF-κB and JNK activation [12]. Nonetheless, the expression of human RIPK4 S376X in Xenopus embryos failed to rescue the severe gastrulation defects caused by Ripk4 deficiency [38]. Therefore, the mutation may cause BPS by inhibiting other RIPK4-mediated signalling pathways, in addition to impairing IRF6 activation.…”
Section: Discussionmentioning
confidence: 84%
“…The GWAS approach has now pointed to several genes involved in the cytoskeleton (Leslie et al 2016a; Leslie et al 2012). Additional molecular evidence on other OFC-related genes further supports regulation of cytoskeletal dynamics in the pathogenesis of OFCs (Biggs et al 2014; Caddy et al 2010; De Groote et al 2015; Leslie et al 2012). Similarly SHROOM3 and NRG1 join a list of genes, including GRHL3, IRF6 , and TFAP2A , required for neurulation that are also implicated in OFCs (Copp and Greene 2013; Kousa et al 2013; Wang et al 2011).…”
Section: Discussionmentioning
confidence: 74%
“…Time-dependent protein induction was studied in HaCaT cells transduced with our inducible vector pDG2iFlag-puro containing the RIPK4 gene (21). Expression of the Flag-tagged transgene could be detected by WB starting 3 h after treatment with 1 g/mL Dox and reached maximal expression levels 9 h after Dox addition (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%